Evolving Guidelines for Retinal Surgeries and Retinopathy of Prematurity (ROP) Treatment Procedures During the COVID-19 Pandemic - Darby E. Santiago, MD; Marie Joan V. Loy, MD; Jeffrey C. Lim, MD; Carlo Antonino L. Nasol, MD; John Alfred H. Lim, MD (Philippine Journal of Ophthalmology)
‎